MANAGEMENT OF MONITORING AND STRENGTHENING THE ROLE OF INTELLIGENCE OF IMMIGRATION IN THE SUPERVISION OF FOREIGN WORKERS IN THE COVID-19 PANDEMIC PERIOD - Felix Ferdin Bakker; Respati Triana Putri; Ale Alfero Deputra (Journal of Law and Border Protection, 2021)
Research on immigration surveillance and intelligence is currently minimal. The supervisory and intelligence functions are the spearhead of implementing guidance and an initial plan to get good results. In general, intelligence is a form of activity to collect data and information, then processed and presented to achieve a goal. Intelligence in the field of immigration aims to detect various threats, challenges, obstacles, and disturbances that can potentially disrupt state security and sovereignty. To obtain such data and information, intelligence activities are carried out. The use of intelligence, especially during the Covid-19 period, is meant that only helpful people can carry out activities in Indonesia, especially foreign citizens, which are expected to positively influence the Indonesian people, including in the fields of research economy, and socio-culture. This research is based on normative juridical research, namely by elaborating each material followed by an existing policy study arrangement. This is intended so that any problems in surveillance and intelligence can be magnified with existing policies. In addition, at this time, the author gives the role of the Indonesian people as a concrete step in providing information for the achievement of the objectives of immigration intelligence to obtain information material that will be considered in reaching a decision.